2012
DOI: 10.1007/s00005-012-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the European Regulatory Framework for Sustainable Bacteriophage Therapy in Human Medicine

Abstract: For practitioners at hospitals seeking to use natural (not genetically modified, as appearing in nature) bacteriophages for treatment of antibiotic-resistant bacterial infections (bacteriophage therapy), Europe's current regulatory framework for medicinal products hinders more than it facilitates. Although many experts consider bacteriophage therapy to be a promising complementary (or alternative) treatment to antibiotic therapy, no bacteriophage-specific framework for documentation exists to date. Decades wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…There is thus no need for a specific set of documentation for bacteriophage therapy [74]. We do not share this opinion for the reasons discussed below.…”
Section: Hurdles In the Current Medicinal Product Development And Markementioning
confidence: 99%
“…There is thus no need for a specific set of documentation for bacteriophage therapy [74]. We do not share this opinion for the reasons discussed below.…”
Section: Hurdles In the Current Medicinal Product Development And Markementioning
confidence: 99%
“…The ability of phages to recognize precisely their hosts, rendered them as favorable antibacterial agents because broad-spectrum antibiotics kill target bacteria along with other beneficial bacteria present in the farm or in the organism body, say intestinal flora [10]. Many studies were applied mainly in the Soviet Union counties showed that application of phages in bacterial therapy or biocontrol is attainable in theory but practicably results were not so successful due to the lack of full coverage of target bacteria and the rapid emergence of bacterial mutations leading to complete resistance against phage infection [11]–[14]. Therefore, phage therapy or phage biocontrol have become unsuccessful [15] and eventually led to replacement of phage therapy with antibiotic treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of bacteriophages as a realistic approach to the control of pathogens has attracted considerable interest in recent years [10],[14] because of the emergence of antibiotic resistant bacteria. For example, calves and piglets with diarrhea due to experimentally administered pathogenic E. coli were cured within 8 h following phage administration [16].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the clinical use of bacteriophages is once again considered as something new. In consequence, the applicants conducting standard clinical trials concerning the use of bacteriophages are forced to begin the clinical study from scratch (15).…”
mentioning
confidence: 99%
“…Bacteriophages should not be classified as a classical therapeutic product, not only because this categorization is scientifically inappropriate, but also it would limit the admission of the product into everyday manufacturing (15).…”
mentioning
confidence: 99%